How We Design Our Study Space during Pandemic Covid-19? - Harsritanto Bangun I R (EDP Sciences, 2021)
The pandemic covid 19 in Indonesia has entered the second year and may be extended into the next several periods of time. As academia, study space has shifted from physical office and class into virtual space. Several design adaptations have been applied in our home to accommodate the preference of users as students/lecturers in teach, work, and study. This study was performed by literature review, questionnaires and software simulation. The result showed that there is a strong relation between virtual space and physical space during a pandemic; the preference of study space design shows a generic template for further developments.